Characterization of Greenbeard Genes Involved in Long-Distance Kind Discrimination in a Microbial Eukaryote - Heller, Jens; Zhao, Jiuhai; Rosenfield, Gabriel; Kowbel, David J.; Gladieux, Pierre; Glass, N. Louise (PLOS Biology, 2016)
This study identifies variable "greenbeard" genes in wild populations of the filamentous fungus Neurospora crassa that affect recognition and chemotropic interactions between germlings and thereby separate the fungal population into communication groups.